Journal of astonishment – a tool to increase satisfaction with exchange programmes - Evelyne N. Rosen; Claus H. Reinhardt (Association for Learning Technology, 2012)
Many medical students use exchange programmes to enrich their portfolio. However, such a confrontation with reality can be challenging because custom and practice sometimes differ radically between countries. Exchange students post specific peculiarities, as encountered by them abroad, onto the medical exchange website. They can ask for the community's help and are expected to describe the (preliminary) solution that they have found. The “journal of astonishment” is structured by country and is designed not only to provide help for current exchange students but also to prepare future students for their stay abroad. Upon conclusion of the exchange, its satisfaction to both student and host institution is evaluated. Following the intervention, non-illness related drop out rates decreased by nearly 30% and student satisfaction improved by 1.7 points on a 10-point satisfaction scale. Host academic institution satisfaction also increased. Postings from the community were considered helpful. Female students especially benefited from the exchange website when preparing for their exchange. The journal of astonishment thus helps students better to select and prepare for an exchange with a particular academic institution. Moreover, the interactive web-based platform can provide spontaneous assistance with problem handling. The journal of astonishment is a low-cost tool that enhances student and host academic institution satisfaction.